Fat necrosis as a differential diagnosis for recurrence in a treated case of breast cancer: A case report - Tippani, Avinassh; Brahmani, Bachu (Indian Journal of Case Reports, 2021)
Fat necrosis is a benign inflammatory process that can involve adipose tissue that most frequently affects peri-menopausal women. It can mimic breast cancer clinically or radiologically. The incidence of breast fat necrosis overall is roughly 0.6%, representing 2.75% of all benign lesions. Fat necrosis presents in 0.8% of breast tumors and 1–9% of breast reduction surgery cases. Most at risk are middle-aged women, with an average age of 50 years, and women with pendulous breasts. Traumatic Fat Necrosis is an important differential diagnosis to be kept in mind in Carcinoma Breast patients who are treated with surgery and adjuvant radiation therapy. We present a case where radiation is followed by a large non-healing ulcer in a known case of breast carcinoma patient.